2014
DOI: 10.1111/jcpe.12323
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled multicentre study comparing short dental implants (6 mm) versus longer dental implants (11–15 mm) in combination with sinus floor elevation procedures. Part 1: demographics and patient‐reported outcomes at 1 year of loading

Abstract: AIM To test whether or not the use of short dental implants (6 mm) results in an implant survival rate similar to long implants (11-15 mm) in combination with sinus grafting. METHODS This multicentre study enrolled 101 patients with a posterior maxillary bone height of 5-7 mm. Patients randomly received short implants (6 mm) (group short) or long implants (11-15 mm) with sinus grafting (group graft). Six months later, implants were loaded with single crowns and patients re-examined at 1 year of loading. Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
167
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(181 citation statements)
references
References 23 publications
6
167
3
5
Order By: Relevance
“…39 The sample size of the present investigation, with 52 patients and 122 implants, is wider than other prospective studies, except for the study by Thoma and colleagues that was a multicenter study involving 4 centres. 17 Findings coming from recent systematic reviews and meta-analyses were in line with our results describing a high prosthesis and implant survival rates for both procedures with no significant differences. [14][15][16] Analysis of pooled data of a systematic review conducted by Thoma and colleagues for EAO working group, 14 documented a 99.5% survival rate for standard implants in augmented sinus and 99.0% for SIs during for a follow-up of 16-18 months, 7,10-12,17 while for shorter follow-up (8-9 months) a 100% survival rate for standard implants and 98.2% for SIs was documented.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…39 The sample size of the present investigation, with 52 patients and 122 implants, is wider than other prospective studies, except for the study by Thoma and colleagues that was a multicenter study involving 4 centres. 17 Findings coming from recent systematic reviews and meta-analyses were in line with our results describing a high prosthesis and implant survival rates for both procedures with no significant differences. [14][15][16] Analysis of pooled data of a systematic review conducted by Thoma and colleagues for EAO working group, 14 documented a 99.5% survival rate for standard implants in augmented sinus and 99.0% for SIs during for a follow-up of 16-18 months, 7,10-12,17 while for shorter follow-up (8-9 months) a 100% survival rate for standard implants and 98.2% for SIs was documented.…”
Section: Discussionsupporting
confidence: 89%
“…Similar high implant survival rates were also documented in other RCTs with the same study design as the present study, but a shorter follow-up. [5][6][7][8][10][11][12]17 Only 2 other published randomized studies reported results after a similar or longer follow-up period, that is 3 years 38 and 5 years. 39 The sample size of the present investigation, with 52 patients and 122 implants, is wider than other prospective studies, except for the study by Thoma and colleagues that was a multicenter study involving 4 centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these regenerative techniques, maxillary sinus augmentation [3][4][5][6][7], guided bone regeneration (GBR) [8], and split-crest techniques [9] are the most commonly used procedures to restore the ideal anatomical bone conditions and to allow simultaneous and/or subsequent placement of dental implants.…”
Section: Introductionmentioning
confidence: 99%
“…Les possibilités de traitements disponibles en fonction du volume osseux résiduel sont bien documentées pour la zone sous-sinusienne. Les techniques de surélévation par voie crestale utilisant des ostéotomes, le comblement de sinus par abord latéral ou même l'association de ces différentes techniques [14][15][16][17] Enfin, comme dans le cas présenté ici, les conséquences de l'inflammation liée à la présence du corps étranger intrasinusien associées à celles de l'intervention nécessaire pour le retirer, peuvent aggraver l'insuffisance de volume osseux résiduel et compromettre le projet prothétique initialement prévu. Il apparaît dès lors nécessaire d'informer clairement le patient en préalable à toute pose d'implant sous-sinusien des éventuelles complications peropératoires et postopératoires, afin d'éclairer sa décision quant aux différentes alternatives thérapeutiques.…”
Section: Discussionunclassified